(untitled) (Bangladesh Journal of Medical Science, 2011)
Background: Hepatitis B virus is a partially double-stranded circular DNA virus and is a member of the Hepadnaviridae family. The virus consists of a core capsid which contains viral DNA and this is surrounded by an envelope containing surface antigen (HBsAg). Both whole, incomplete virus particles, consisting entirely of HBsAg, are produced during replication of HBV. The HBsAg particles vary greatly in morphology and are found in high concentrations in early acute infection and continue to be produced in chronic disease.1 Objectives: Diagnostic potential of Hepatitis-B surface antigen (HBsAg) positivity and its prevalence was evaluated among volunteers from various localities in Solapur District, Maharashtra State, India. Methodology: The prevalence of hepatitis B surface antigen (HBsAg) was studied from Solapur, Maharashtra State, India, among 767 volunteers (male 470 and female 297), aged 05-55 years volunteers, who required medical check-ups. Blood samples, collected during March to May 2010, were tested for HBsAg using a third-generation ELISA kit. Results: Of the 767 volunteers, male 1.82% and female 1.17% were positive for HBsAg. The results revealed that hepatitis B infection in the target group was below the intermediate endemicity. Conclusion: This study demonstrates that proper training of new entrants in the medical field can be pivotal in preventing HBsAg and it is advocated that a programme for education, vaccination and prophylaxis must be implemented in all healthcare set ups. Key words: HBsAg; Hepatitis B surface antigen; HEPALISA; Jaundice; seroprevalence. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7803 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.91-94